Surface immunogenic protein from Streptococcus agalactiae and Fissurella latimarginata hemocyanin are TLR4 ligands and activate MyD88- and TRIF dependent signaling pathways - Díaz-Dinamarca, Diego A.; Salazar, Michelle L.; Escobar, Daniel F.; Castillo, Byron N.; Valdebenito, Bastián; Díaz, Pablo; Manubens, Augusto; Salazar, Fabián; Troncoso, Mayarling F.; Lavandero, Sergio; Díaz, Janepsy; Becker, María Inés; et al. (Frontiers in Immunology, 2023)
The development of vaccine adjuvants is of interest for the management of chronic diseases, cancer, and future pandemics. Therefore, the role of Toll-like receptors (TLRs) in the effects of vaccine adjuvants has been investigated. TLR4 ligand-based adjuvants are the most frequently used adjuvants for human vaccines. Among TLR family members, TLR4 has unique dual signaling capabilities due to the recruitment of two adapter proteins, myeloid differentiation marker 88 (MyD88) and interferon-β adapter inducer containing the toll-interleukin-1 receptor (TIR) domain (TRIF). MyD88-mediated signaling triggers a proinflammatory innate immune response, while TRIF-mediated signaling leads to an adaptive immune response. Most studies have used lipopolysaccharide-based ligands as TLR4 ligand-based adjuvants; however, although protein-based ligands have been proven advantageous as adjuvants, their mechanisms of action, including their ability to undergo structural modifications to achieve optimal immunogenicity, have been explored less thoroughly. In this work, we characterized the effects of two protein-based adjuvants (PBAs) on TLR4 signaling via the recruitment of MyD88 and TRIF. As models of TLR4-PBAs, we used hemocyanin from Fissurella latimarginata (FLH) and a recombinant surface immunogenic protein (rSIP) from Streptococcus agalactiae. We determined that rSIP and FLH are partial TLR4 agonists, and depending on the protein agonist used, TLR4 has a unique bias toward the TRIF or MyD88 pathway. Furthermore, when characterizing gene products with MyD88 and TRIF pathway-dependent expression, differences in TLR4-associated signaling were observed. rSIP and FLH require MyD88 and TRIF to activate nuclear factor kappa beta (NF-κB) and interferon regulatory factor (IRF). However, rSIP and FLH have a specific pattern of interleukin 6 (IL-6) and interferon gamma-induced protein 10 (IP-10) secretion associated with MyD88 and TRIF recruitment. Functionally, rSIP and FLH promote antigen cross-presentation in a manner dependent on TLR4, MyD88 and TRIF signaling. However, FLH activates a specific TRIF-dependent signaling pathway associated with cytokine expression and a pathway dependent on MyD88 and TRIF recruitment for antigen cross-presentation. Finally, this work supports the use of these TLR4-PBAs as clinically useful vaccine adjuvants that selectively activate TRIF- and MyD88-dependent signaling to drive safe innate immune responses and vigorous Th1 adaptive immune responses.